2017
DOI: 10.1099/jgv.0.000712
|View full text |Cite
|
Sign up to set email alerts
|

Viral dependence on cellular ion channels – an emerging anti-viral target?

Abstract: The broad range of cellular functions governed by ion channels represents an attractive target for viral manipulation. Indeed, modulation of host cell ion channel activity by viral proteins is being increasingly identified as an important virus-host interaction. Recent examples have demonstrated that virion entry, virus egress and the maintenance of a cellular environment conducive to virus persistence are, in part, dependent on virus manipulation of ion channel activity. Most excitingly, evidence has emerged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 55 publications
1
71
0
2
Order By: Relevance
“…In this study, time of addition experiments and the progression of labelled viruses showed that the effect of cholesterol depletion on BUNV was not at the initial stage of cell penetration, but occurred during the time period when the virus escapes from the endocytic pathway. Furthermore, we showed that cholesterol depletion reduced K + accumulation in the endocytic network, leading us to question whether the role of cholesterol in BUNV entry was linked to endosomal K + homeostasis, a factor we have shown to be critical for BUNV and HAZV entry (17, 36,41).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, time of addition experiments and the progression of labelled viruses showed that the effect of cholesterol depletion on BUNV was not at the initial stage of cell penetration, but occurred during the time period when the virus escapes from the endocytic pathway. Furthermore, we showed that cholesterol depletion reduced K + accumulation in the endocytic network, leading us to question whether the role of cholesterol in BUNV entry was linked to endosomal K + homeostasis, a factor we have shown to be critical for BUNV and HAZV entry (17, 36,41).…”
Section: Discussionmentioning
confidence: 99%
“…An important difference we had previously observed between TLR7 and TLR8 signaling on CD4 + T cells was an increase in intracellular Ca 2+ triggered by TLR7 stimulation that did not occur after ssRNA40 stimulation (68). As Ca 2+ signaling has been involved in the phenotype of APC and it is an important modulator of cell responses during viral infections (69,70), we decided to examine whether TLR7 stimulation induced an increase in intracellular Ca 2+ concentration in monocytes (Fig 9A). Unlike ssRNA40, IMQ stimulation induced a significant increase in intracellular Ca 2+ concentration in a dose-dependent manner (Fig 9A).…”
Section: Tlr7-dependent Ca 2+ Signaling Inhibits Type I Ifn Responsementioning
confidence: 93%
“…the specific routes of endosomal translocation and the host factors required during trafficking to the ER remain largely undefined. Whilst it has long been understood that the acidification of endosomes is essential for PyV entry cues, the endosomal balance of other ions and their crucial roles during the infection of a plethora of viruses is only beginning to emerge (15, 39).…”
Section: Discussionmentioning
confidence: 99%